Case Series: Carbon Dioxide Cryo-Assisted Surgery: Making the Difference in the Management of Keloids and Hypertrophic Scars in a Resource-Limited Setting - Gbeneol, T. J.; Aria, O. N. (British Journal of Healthcare and Medical Research, 2025)
Background: A number of illnesses and disorders, including both benign and malignant skin ailments, have been treated with cryosurgery in the past. For a variety of benign skin conditions, cryosurgery is an incredibly effective treatment. Family doctors are capable of swiftly learning the method with the right guidance and supervised practice. When it comes to treating lesions in the majority of non-hair-bearing body parts, cryosurgery works best for patients with light skin. Materials & Method: a six (6) months study in a Plastic Surgery Centre, with 136 patients treated with CO2 Cryo-assisted surgery were monitored over a 5 year period. Result: From our study 85% of our wounds healed without regrowth or recurrence. The 15% which show evidence of regrowth (recurrence); and were injected with Intradermal 5 FluoroUracil and Triamcenolone in a ratio mix of 3:1. The scar was subsequently reviewed at 2-4 weekly interval. A heaping up scar is reinjected intra-lesionally and intradermally. Conclusion: Another alternative for frequently occurring dermatological lesions is cryosurgery, which is minimally invasive, fast, efficient, and requires little to no anesthesia. Cryosurgery is a fantastic advantage for patients and caregivers similarly, because it is less intrusive, requires no cones or sutures, and requires no post-operative care. Comparing CO2 to argon, helium, liquid nitrogen, nitrous oxide, and other gases, it is more readily available, less expensive, and has a longer shelf life.